THE INFLUENCE OF THE "O" TECHNOLOGY OF TILLAGE AND MINERAL FERTILIZERS ON THE WATER-FOOD REGIME AND YIELD OF CHICKPEAS IN THE BOGAR OF UZBEKISTAN - H.Y. Yusupov; A. Mamatkulov; Pokrovskaya M.N. (Scholars Digest Publishing, 2023)
The article presents the results of studies conducted in conditions of semi-moisture-rich bogara of Uzbekistan to study the influence of "O" technology, mineral fertilizers, biofertilizers on the dynamics of the water-food regime of the soil and the yield of a new variety of chickpeas "Gulistan". It has been established that a more favorable water-food regime of the soil for chickpeas during the growing season is formed by direct sowing of seeds with a stubble grain planter SZS-2.1.
Keywords: bogara, crop rotation,